Development of microalgae as a biopharming platform - Els, Johann Hendrik (Department of Molecular and Cell Biology, 2022)
Microalgae may be a powerful biopharmaceutical production platform that is still in its infancy of development. The research done in this project tested the feasibility of creating algal cell packs, a novel immobilised microalgae transient production platform for the expression of recombinant protein. First it had to be established whether the available plant expression vectors could be used for the transfer of genetic material into packed microalgae. The method showed successful transfer of the neomycin phosphotransferase II resistance gene (nptII). Further experiments analysed the plant expression vectors pTRAc and pRIC3.0 for expression of enhanced green fluorescent protein (EGFP) in Scenedesmus spp. by western blotting. Possible replication of the plant geminivirus-derived pRIC3.0 was then confirmed by comparing to replication in Nicotiana benthamiana by quantitative polymerase chain reaction (qPCR). Western blot results indicated EGFP expression in N. benthamiana but not in Scenedesmus. By using PCR the presence of EGFP DNA in Scenedesmus was detected but qPCR showed no increase of the pRIC3.0 replicon. Despite no detection via antibodies of EGFP in Scenedesmus, green fluorescence was observed. These initial results showed promise and points to a system that requires optimisation for increased transfection rates and protein expression. Following on from the initial work, the project set out to determine the feasibility of expressing a recombinant anti-Ebola viral inhibitor protein in three different plant based platforms namely N. benthamiana, a microalgal genus, Desmodesmus and a BY2 tobacco plant-cell culture. Protein expression was compared between the Desmodesmus algal cellpack, N. benthamiana plant expression system and BY-2 plant cell packs by western blotting. Four designs of the viral inhibitor fused to the maize ƴ-zein protein body inducing protein, ZERA, were expressed in trace quantities. Transient expression was more prominent in the algal cell packs than in N. benthamiana and BY-2 cells. The algal cell pack system may potentially be a powerful tool to test recombinant protein expression in a range of microalgal hosts via Agrobacterium-mediated genetic transfection. The future development of recombinant protein expression platforms could be enhanced by rapid testing of protein production in different species. Refinement needs to be done on the algal cell pack to increase transfection efficiency and expression in microalgae to produce commercially viable quantities of heterologous protein.